2020
DOI: 10.1021/acs.jpclett.0c01600
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Vanadium(V) Oxide in Hybrid Hole Transport Layer Enables Long-term Operational Stability of Perovskite Solar Cells

Abstract: Recent studies have shown that charge transport interlayers with low gas permeability can increase the operational lifetime of perovskite solar cells serving as a barrier for migration of volatile decomposition products from the photoactive layer. Herein we present a hybrid hole transport layer (HTL) comprised of p-type polytriarylamine (PTAA) polymer and vanadium(V) oxide (VO x ). Devices with PTAA/VO x top HTL reach up to 20% efficiency and demonstrate negligible degradation after 4500 h of light soaking, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…According to the literature, such configuration allows achieving high operational stabilities and competitive efficiencies for ZnO-based PSCs [43]. The stability evaluation was performed in the lightsoaking chamber's (Figure 3b) built-in glovebox with an inert atmosphere and control of oxygen and water concentration <0.01 ppm [16]. The unencapsulated devices were exposed to the constant illumination of high-power white light-emitting diodes (70 ± 3 mW/cm 2 ) and a temperature of 45 ± 1 • C for 1250 h, which corresponded to the recommended degradation protocol ISOS-L-2I [44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, such configuration allows achieving high operational stabilities and competitive efficiencies for ZnO-based PSCs [43]. The stability evaluation was performed in the lightsoaking chamber's (Figure 3b) built-in glovebox with an inert atmosphere and control of oxygen and water concentration <0.01 ppm [16]. The unencapsulated devices were exposed to the constant illumination of high-power white light-emitting diodes (70 ± 3 mW/cm 2 ) and a temperature of 45 ± 1 • C for 1250 h, which corresponded to the recommended degradation protocol ISOS-L-2I [44].…”
Section: Resultsmentioning
confidence: 99%
“…In brief, it was demonstrated that the SiO x thin layer and reduced MO x layers appeared between Si and MO x , leading to Fermi level equilibration across the interface [14]. In addition, such advantages of MO x , with high conductivity and the ability to form a smooth pinholefree layer with organic HTLs, enable high efficiencies in PSCs of more than 20% [15,16]. Additionally, the high transparency of MO x permits their application in inverted PSC configurations [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hole‐collecting electrode consisting of MoO x (10 nm) and Ag (100 nm) was deposited using thermal evaporation, resulting in the final configuration of ITO/SnO 2 /PCBA/CH 3 NH 3 PbI 3 /HTL/MoO x /Ag (Figure 5b). [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…Further, an imperfect interface at the perovskite/SOOM causes high resistance, low transport, and high interfacial recombination ( Figure 8 a); however, research on well‐established methods for depositing SOOMs on top of perovskite is lacking. [ 108–110 ] Although HPSCs with SOOMs are usually expected to be very stable under humid, light, and thermal stress conditions because of their structural stability, the perovskite/SOOM interface might suffer from a certain degradation mechanism that should be suppressed to ensure the stability of HPSCs. [ 76,109 ] For instance, during the thermal degradation of the perovskite/NiO interface, the large negative enthalpy of the NiO reaction with HI arising from MAI causes the formation of NiI 2 (Figure 8a).…”
Section: Challenges and Promising Strategies For High‐performance Hpscsmentioning
confidence: 99%